Environmental Education in the teaching–learning process: A Study at the Mukolongondjo (Research, Society and Development, 2026)
This article investigates environmental education in the teaching–learning process at the Primary Teacher Training College of Mukolongondjo, Angola, aiming to develop didactic actions that promote environmental knowledge and preservation. The main objective is to propose educational strategies that involve teachers, students, and the community, strengthening environmental awareness and attitudes. The methodology adopted combines a mixed approach (qualitative and quantitative), including bibliographic research, a case study, interviews, questionnaires, observation, and document analysis. The study population includes teachers, students, school management, and the school community. The data reveal difficulties in the implementation of environmental education, such as limited teacher training, lack of institutional policy, and low student engagement, with students showing limited knowledge of the subject. The results indicate that, despite recognizing its importance, there are obstacles to effective implementation, highlighting the need for continuous training, participatory actions, and contextualized practices. The main discussions emphasize the importance of innovative pedagogical strategies, an interdisciplinary approach, and greater involvement of the entire school community in environmental practices. As recommendations, practical didactic actions are proposed, such as ecological walks, awareness projects, tree planting, and cultural activities, in order to transform the school into a space for environmental awareness and responsibility. Thus, the study contributes to strengthening environmental education in the school context, promoting a more responsible generation committed to sustainability.